Interconsultas al Servicio de Otorrinolaringología en el Hospital Clínico Universidad de Chile - Bahamonde S., Hector; Ortúzar G., Esteban; Valdés P., Constanza; Ullrich G., Constanza; Zerega R., Mario (Revista Hospital Clínico Universidad de Chile, 2010)
The objective of this paper is to analyze the consultations performed by the Ear, Nose and Throat service from Hospital Clínico Universidad de Chile (HCUCH) in other services of the hospital during the year 2006. Using a random sample of 80 consultations we find that the services most consulted were: internal medicine (37,5%), surgery (13,8%), and pediatrics (13,5%). The leading causes were swallowing disorders (30%), prolonged mechanic ventilation (12,5%), and hypoacusia (11,3%). The average answer time was 1,28 days (with standard deviation of 2.5 days), 41,3% were followed with a median of 2 controls by patient (interquartile range 2-4). Furthermore 35% of the sample was intubated. The mean time of intubation versus the accepted recommendation was 15,7 vs 10 days (t-test p< 0,0005). 13,3% of tracheostomy where performed by ORL. High answer time, in the case of swalling disorder, is due to lack ofmaterials. Complications of tracheostomy are less frequent and severe.